Garlic burn trauma of the oral mucosa in a patient with trigeminal neuralgia: A case report - Tomo, Saygo; Santos, Ingrid da Silva; Cruz, Thiago Moreira da; Miyahara, Glauco Issamu [UNESP]; Simonato, Luciana Estevam (Wiley, 2022)
Garlic is one of the most common medicinal plants used since ancient times to treat diverse diseases within several cultures worldwide. Nevertheless, this plant has the potential to cause chemical burns of the skin and mucosa. This report presents a case of a garlic burn in the palate of a 57-year-old woman who applied garlic to the palate to relieve the pain of trigeminal neuralgia. This case demonstrates the potential of garlic to cause chemical burns to the oral mucosa and raises an alert to oral health professionals regarding inappropriate self-treatment methods.
Keywords: chemical burn; garlic burn; oral mucosa; trigeminal neuralgia